Genes associated with rheumatoid arthritis and mild inflammatory arthritis. II. Association of HLA with complement C3 and immunoglobulin Gm allotypes. Issue 4 (April 1990) - Puttick, A H; Briggs, D C; Welsh, K I; Williamson, E A; Jacoby, R K; Jones, V E
Abstract : Associations were sought between major histocompatibility complex (MHC) genes on chromosome 6 and the complement component C3 and immunoglobulin genes located on other chromosomes which might contribute to susceptibility to mild inflammatory arthritis (IA) or definite rheumatoid arthritis (RA). Frequencies of the complement C3F allele were raised in patients with IA but were normal in patients with RA and controls. When associations between C3F and MHC genes were sought frequencies of some MHC genes were greater in patients with C3F than in those without–for example, HLA-B8 and DR3 in patients with RA and DR2 in patients with IA. Conversely, DR4 frequency was lower in patients with IA with C3F than in those without. Thus the C3F allele may act independently or exert an epistatic effect on MHC genes to increase susceptibility or protect against disease. The frequency of the immunoglobulin heavy chain allotype Glm(2) on chromosome 14 was increased in patients with RA but only in those with the phenotype Gm1, 2, 3, 17;21, 5; no significant associations were found between MHC genes and Gm phenotypes. Further, no associations of MHC, C3F, and immunoglobulin genes were shared by patients with RA and those with IA, indicating a different genetic basis for the two clinical entities.